2020
DOI: 10.18517/ijaseit.10.6.9478
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive Measurement of Lycopene Content in High Soluble Solids Stored Tomato (Solanum Lycopersicum Mill. cv Rinka 409)

Abstract: High-quality fruits can be produced by controlling the environmental factors, i.e. temperature, relative humidity, carbon dioxide, and light intensity. The tomato (Solanum lycopersicum) variety 'Rinka 409', was grown hydroponically with a high-wire system in high technology greenhouse, Ehime University, Japan. The water stress treatment using visual monitoring system was used to produce the high soluble solids tomato fruits. Moreover, a high lycopene content of tomato can be produced by controlling the storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In addition, PLS is a non-parametric, multivariable approach for predicting the calibration model that assigns the response variable y to an x-predictor group [26], [27]. Based on research conducted by Anggraeni [28] and Hayati [29] on the comparison of PLS methods with principal component regression (PCR), it was shown that the PLS method provides optimum results. The reference and spectra data were used to develop calibration models for determining the total carotene and vitamin C.…”
Section: F Data Analysismentioning
confidence: 99%
“…In addition, PLS is a non-parametric, multivariable approach for predicting the calibration model that assigns the response variable y to an x-predictor group [26], [27]. Based on research conducted by Anggraeni [28] and Hayati [29] on the comparison of PLS methods with principal component regression (PCR), it was shown that the PLS method provides optimum results. The reference and spectra data were used to develop calibration models for determining the total carotene and vitamin C.…”
Section: F Data Analysismentioning
confidence: 99%
“…Horticultural products can also use this NIR method in grading, sorting, internal quality, and determining harvest time [5]. Determination of the quality of horticultural products can be done non-destructively by using NIR spectroscopy that has been applied to watermelon [6] and melon [7], using spectral for detection Lycopene Content in Tomato [8], detection of mango quality [9], [10].…”
Section: Introductionmentioning
confidence: 99%